The effects of titanium dioxide (TiO2) nanoparticles on physiological, biochemical, and antioxidant properties of Vitex plant (Vitex agnus - Castus L) - Seyed Mostafa Moshirian Farahi; Mohammad Ehsan Taghavizadeh Yazdi; Elham Einafshar; Mahdi Akhondi; Mostafa Ebadi; Shahrouz Azimipour; Homa Mahmoodzadeh; Alireza Iranbakhsh (Heliyon, 2023)
Titanium dioxide nanoparticles (TiO2NPs) are widely used in agriculture in order to increase the yield and growth characteristics of plants. This study investigated the effects of TiO2NPs on photosynthetic pigments and several biochemical activities and antioxidant enzymes of the Vitex plant. Different concentrations of nanoparticles (0, 200, 400, 600 and 800 ppm) at five levels were sprayed on Vitex plants on the 30th day of the experiment. TiO2NPs at different concentrations had positive effects on root and shoot dry weight and a negative effect on leaf dry weight. The amount of chlorophyll increased with the concentration of TiO2NPs; however, the amount of chlorophyll b showed a decreasing trend while the total chlorophyll had a constant trend. The highest amount of soluble sugar was obtained in the treatment of 200 ppm nanoparticles. The application of TiO2NPs did not have any effect on the content of proline and soluble proteins of Vitex plant. The effects of foliar TiO2NPs, compared to the control, showed a significant increase in the activity of antioxidant enzymes. In general, TiO2NPs had a favorable effect on dry matter production and some antioxidant and biochemical properties of the Vitex plant.